Determinan Tingkat Efisiensi Perbankan di Indonesia - Veronika Cindy Mey Tika Sari; Puji Nurhayati; Tiya Dzuralda (Akuntabilitas, 2022)
Indonesia is a country with the existence of a Sharia banking sector that operates side by side with conventional banks under the supervision of Bank Indonesia which is quite a lot. The existence of Islamic banking needs to be measured efficiency in measuring the resilience of its market share. This study aims to determine the factors that affect the level of efficiency of Islamic banking in Indonesia for the period 2010-2021, which is projected with Non Performing Loan (NPL), size, Capital Adequency Ratio (CAR), Return On Assets (ROA), Financing to Deposit Ratio (FDR). The data used is secondary data in the form of islamic banking annual reports. This research sample is Sharia Commercial Bank as many as 7 Banks. Sampling techniques are carried out using purposive sampling. Data analysis techniques use multiple linear regression analysis with SPSS v.18. The results showed that Non Performing Loans (NPL), size, and Return On Assets (ROA) affected the bank’s efficiency rate. Meanwhile, Capital Adequency Ratio (CAR) and Financing to Deposit Ratio (FDR) have no effect on the bank’s efficiency level.